2014
DOI: 10.1016/j.bbapap.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between tachyplesin I, an antimicrobial peptide derived from horseshoe crab, and lipopolysaccharide

Abstract: Lipopolysaccharide (LPS) is a major constituent of the outer membrane of Gram-negative bacteria and is the very first site of interactions with antimicrobial peptides (AMPs). In order to gain better insight into the interaction between LPS and AMPs, we determined the structure of tachyplesin I (TP I), an antimicrobial peptide derived from horseshoe crab, in its bound state with LPS and proposed the complex structure of TP I and LPS using a docking program.CD and NMR measurements revealed that binding to LPS sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 38 publications
3
65
0
Order By: Relevance
“…With potent and broad-spectrum activity against both Gram-positive and Gram-negative bacteria, tachyplesin I was a promising candidate for development of antiinfection, antitumor, and antivirus drugs. Previous studies showed that tachyplesin I can kill bacteria by permeabilizing the bacterial membrane and acting on intracellular targets in bacteria to inhibit DNA, RNA, and protein synthesis and enzyme activity (11)(12)(13). Tachyplesin I acts similarly to magainin-2, MSI-78, and LL-37 by forming a toroidal transmembrane pore (14).…”
mentioning
confidence: 99%
“…With potent and broad-spectrum activity against both Gram-positive and Gram-negative bacteria, tachyplesin I was a promising candidate for development of antiinfection, antitumor, and antivirus drugs. Previous studies showed that tachyplesin I can kill bacteria by permeabilizing the bacterial membrane and acting on intracellular targets in bacteria to inhibit DNA, RNA, and protein synthesis and enzyme activity (11)(12)(13). Tachyplesin I acts similarly to magainin-2, MSI-78, and LL-37 by forming a toroidal transmembrane pore (14).…”
mentioning
confidence: 99%
“…Due to their small size, positive net charge, and amphiphatic character, they are able to insert into bacterial membranes and to interact with the negatively charged lipopolysaccharides in bacterial membranes [160][161][162]164] such as lipopolysaccharides [166]. This probably leads to permeabilization and disruption of bacterial plasma membranes [166,167]. More recent studies confirmed the antibacterial activity of tachyplasins [168,169] and showed that these compounds also exhibit antiviral [170], antiparasitic [171], and anticancer effects [172].…”
Section: Horseshoe Crab-derived Antibioticsmentioning
confidence: 67%
“…Indeed, these compounds were found to inhibit the growth of both Gram-negative and -positive bacteria at low concentrations [161,164,165]. Due to their small size, positive net charge, and amphiphatic character, they are able to insert into bacterial membranes and to interact with the negatively charged lipopolysaccharides in bacterial membranes [160][161][162]164] such as lipopolysaccharides [166]. This probably leads to permeabilization and disruption of bacterial plasma membranes [166,167].…”
Section: Horseshoe Crab-derived Antibioticsmentioning
confidence: 99%
“…In particular, a parallel emerges with the fish defense peptides, pardaxins, where adaptive changes in the overall peptide shape enable binding to lipid A head groups as well as to hydrophobic fatty acyl chains [78]. A similar pattern of interaction was also observed between LPS and the horseshoe crab major AMP, tachyplesin 1 [79]. …”
Section: Resultsmentioning
confidence: 99%